Analisis Strukturalisme Genetik Goldman dalam Cerpen Gadis Minang dan Bunga Sakura di Kepalanya Karya Anugrah Ghani - Wulandari, Annisa; Afni, Yulia; Siregar, Ramah Atika (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2023)
The purpose of the research is to describe the intrinsic structure and genetic structure of the short story "Gadis Minang dan Bunga Sakura di Kepalanya" by Anugrah Ghani. The research was conducted using descriptive qualitative method with in-depth data interpretation. The findings show that structurally the short story "Gadis Minang dan Bunga Sakura di Kepalanya" has intrinsic elements that build the cohesion of the short story, namely theme, character and characterization, plot, setting, time setting, and social setting. Meanwhile, the genetic structure found is the human facts of the collective subject, the author's worldview and the dialectic of explanatory understanding. Human facts in this short story illustrate the existence of social realities such as social activities that often occur in short stories are parents who disagree with their children's dreams as if they do not believe in a child. Furthermore, the collective subject illustrates that the Minang girl is always bound by a condition where she cannot decide her own life path and it is difficult to deny the bond called culture. The author's worldview describes the author's world perspective on the life of a Minang girl who has a uniqueness or specialty, such as a cherry blossom on her head. The author uses this element to convey a message about diversity, unique beauty. The dialectic of understanding and explanation describes a shocking story with a focus on the impact of decisions and attitudes on one's dreams. The loss of a child elicits various emotional reactions from the family and the neighborhood. The symbolism of the wounded twilight creates a sense of sadness and emptiness, along with the tragic end of the Minang girl who was expected to leave for Sakura country.